2015
DOI: 10.1371/journal.pone.0124707
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeography of a Marine Insular Endemic in the Atlantic Macaronesia: The Azorean Barnacle, Megabalanus azoricus (Pilsbry, 1916)

Abstract: The Azorean barnacle, Megabalanus azoricus (Pilsbry, 1916), is a Macaronesian endemic whose obscure taxonomy and the unknown relationships among forms inhabiting isolated Northern Atlantic oceanic islands is investigated by means of molecular analysis herein. Mitochondrial data from the 16S rRNA and COX1 genes support its current species status, tropical ancestry, and the taxonomic homogeneity throughout its distribution range. In contrast, at the intraspecific level and based on control region sequences, we d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 76 publications
0
4
0
Order By: Relevance
“…Multiple host species' distributions overlap in waters around South Africa, including two with enormous ranges in the southern hemisphere (Table S1), and this region potentially bridges to the northern hemisphere through a common eastern Atlantic host species (E. spinax). In attempting to estimate time of the earliest haplotype divergence (approximate time of origin of Anelasma as a new species), we obtained from the literature maximum and minimum values for COI and control region mutation rates for related barnacle species, where fossil records or geographical events allowed reliable estimates [7]. The calculated divergence times were found to be between 274,000 and 545,000 ya for the COI gene, and between 408,000 and 811,000 ya for the control region (see Supplemental Experimental Procedures for details).…”
Section: Magazinementioning
confidence: 99%
“…Multiple host species' distributions overlap in waters around South Africa, including two with enormous ranges in the southern hemisphere (Table S1), and this region potentially bridges to the northern hemisphere through a common eastern Atlantic host species (E. spinax). In attempting to estimate time of the earliest haplotype divergence (approximate time of origin of Anelasma as a new species), we obtained from the literature maximum and minimum values for COI and control region mutation rates for related barnacle species, where fossil records or geographical events allowed reliable estimates [7]. The calculated divergence times were found to be between 274,000 and 545,000 ya for the COI gene, and between 408,000 and 811,000 ya for the control region (see Supplemental Experimental Procedures for details).…”
Section: Magazinementioning
confidence: 99%
“…Among the three archipelagos, Azores, Madeira and Canary Islands, sister areas tend to change depending on the taxa/phylum used for the biogeography study. For instance, based on the species composition of ichtyofauna (Lloris et al 1991), Cirripedia (Quinteiro et al 2015) and shallow subtidal macroalgae (Sangil et al 2018), the Lusitanian Macaronesia has been divided into two biogeographic areas, one comprising Madeira and the Canary Islands and the other comprising only the Azores. One the other hand, Vanderpoorten et al (2007) and later Tuya and Haroun (2009) featured Azores and Madeira as sister areas based on algae and pteridophyte diversity.…”
Section: Introductionmentioning
confidence: 99%
“…These islands, just off the coast of Europe and Africa, are formed by volcanic seamounts and were never part of a continent. This makes the biogeography of the islands very attractive for phylogeographic studies (Quinteiro et al, ; Stefanni et al, ; Whittaker, ). The marine environment is very often characterised as having complex oceanic currents and no physical barriers, which greatly increase a species’ dispersal potential, promoting high gene flow over large scales (Selkoe et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…These currents, together with the apparent lack of physical barriers, can strengthen the potential for gene flow. Indeed, several phylogeographic studies have reported a low population genetic differentiation in the Macaronesian region for different taxa, including gastropods (De Wolf et al, ), crustaceans (Faria et al, ; Quinteiro et al, ) and fishes (Francisco et al, ; Stefanni et al, ). On the other hand, the Macaronesia archipelagos are also characterised by different upwellings zones, habitat discontinuities and ecotones between areas with different environmental properties and areas with historical sea level drops ( e.g ., Stefanni et al, ).…”
Section: Introductionmentioning
confidence: 99%